“When green turns dark”: some reflections on human rights and renewable energies in the framework of international law, making some reference to the case of Sardinia (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The European Union has set the ambitious goal of achieving climate neutrality by 2050. The energy transition is fundamental for achieving this objective, and requires to increase the use of renewable energies, according to Directive 2018/2001. However, it is necessary to ensure the consistency of the energy transition with human rights and the principles of intergenerational equity, environmental justice, self-determination as well as permanent sovereignty over natural resources. This study analyses this complex issue from the perspective of international law, while making some reference to the Sardinian case, since it has inspired this research.
Keywords: Renewable energies; energy transition; environmental justice; human rights; Sardinia